2022
DOI: 10.1371/journal.pone.0271910
|View full text |Cite|
|
Sign up to set email alerts
|

Viraemic-time predicts mortality among people living with HIV on second-line antiretroviral treatment in Myanmar: A retrospective cohort study

Abstract: Introduction Despite HIV viral load (VL) monitoring being serial, most studies use a cross-sectional design to evaluate the virological status of a cohort. The objective of our study was to use a simplified approach to calculate viraemic-time: the proportion of follow-up time with unsuppressed VL above the limit of detection. We estimated risk factors for higher viraemic-time and whether viraemic-time predicted mortality in a second-line antiretroviral treatment (ART) cohort in Myanmar. Methods We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…A study from Myanmar reported that among PLHIV with viraemic time of 50–79% or >80%, mortality hazard was almost threefold higher compared with those who were not viraemic during their follow-up time (aHR 2.92 [95% CI 1.21 to 7.10], p=0.02; aHR 2.71 [95% CI 1.22 to 6.01], p=0.01, respectively). 29 In the same study, mortality hazard was not increased in participants with a viraemic time <50% of their follow-up. Similarly, Quiros-Roldan et al.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…A study from Myanmar reported that among PLHIV with viraemic time of 50–79% or >80%, mortality hazard was almost threefold higher compared with those who were not viraemic during their follow-up time (aHR 2.92 [95% CI 1.21 to 7.10], p=0.02; aHR 2.71 [95% CI 1.22 to 6.01], p=0.01, respectively). 29 In the same study, mortality hazard was not increased in participants with a viraemic time <50% of their follow-up. Similarly, Quiros-Roldan et al.…”
Section: Resultsmentioning
confidence: 86%
“…Cumulative viraemia was defined as the proportion of the follow-up time on ART under or over a certain VL threshold 16 , 17 , 26 , 27 , 29 , 35–37 , 43 or both 16 , 17 , 26 , 27 , 36 , 37 or as viraemia copy-years (VCY; or a variation of this definition), which estimates the area under a patient's VL curve 23 , 24 , 28 , 32 , 33 , 35 , 38–42 , 44–46 (Table 1 ). The method was first presented by Cole et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, protracted periods of poor adherence with longer viremic time will result in virological and immunological failure and ultimately death. 17 Adjusted Cox regression analyses found the relative mortality risk was elevated by 49% to 75% in people with 1, 2, or ≥2 VL tests >1000 copies/mL during secondline treatment, respectively. The highest proportion of deaths and losses were in the group who had not been taking second-line regimens for long enough to quality for VL testing, or perhaps had disengaged from care, and in this group without a VL test, the adjusted HR for death was 6.40 (95% CI 5.91-6.93).…”
mentioning
confidence: 99%